Node mobility scheme in emergency multi-hop wireless network - Kangrong ZHANG; Jiming LIN; Lin ZHENG (物联网学报)
When there is a segmentation phenomenon in the network,the increase in throughput easily leads to network congestion.The key problem that causes network segmentation is that there are key nodes in the network.The key nodes are public nodes of a large number of network routes,which lead to the increase of energy consumption of key nodes and the decrease of network communication efficiency.A node mobility scheme based on dependency graphs to compensate for network segmentation was proposed.Firstly,the key nodes that cause congestion in the network were determined through the dependency graph.Then,the neighboring points of the key nodes were selected.Under the condition that the topology of the nodes were unchanged,moving in the divection of the shortest connected distance to establish a backup route of the key node position.The simulation results show that compared with the existing node mobility schemes,this scheme has significant performance improvements in network connectivity,coverage and network life cycle.